A Supramolecular‐Based Dual‐Wavelength Phototherapeutic Agent with Broad‐Spectrum Antimicrobial Activity Against Drug‐Resistant Bacteria - Yu, Zhi‐Hao; Li, Xingshu; Xu, Fugui; Hu, Xi‐Le; Yan, Jiatao; Kwon, Nahyun; Chen, Guo‐Rong; Tang, Tingting; Dong, Xiaojing; Mai, Yiyong; Chen, Daijie; Yoon, Juyoung; et al. (Angewandte Chemie International Edition, 2020)
With the ever‐increasing threat posed by the multi‐drug resistance of bacteria, the development of non‐antibiotic agents for the broad‐spectrum eradication of clinically prevalent superbugs remains a global challenge. Here, we demonstrate the simple supramolecular self‐assembly of structurally defined graphene nanoribbons (GNRs) with a cationic porphyrin (Pp4N) to afford unique one‐dimensional wire‐like GNR superstructures coated with Pp4N nanoparticles. This Pp4N/GNR nanocomposite displays excellent dual‐modal properties with significant reactive‐oxygen‐species (ROS) production (in photodynamic therapy) and temperature elevation (in photothermal therapy) upon light irradiation at 660 and 808 nm, respectively. This combined approach proved synergistic, providing an impressive antimicrobial effect that led to the complete annihilation of a wide spectrum of Gram‐positive, Gram‐negative, and drug‐resistant bacteria both in vitro and in vivo. The study also unveils the promise of GNRs as a new platform to develop dual‐modal antimicrobial agents that are able to overcome antibiotic resistance. Antibacterial steamroller: Polycationic porphyrin and water‐dispersible graphene nanoribbons self‐assemble into a supramolecular nanocomposite that combines both photodynamic and photothermal therapy for the treatment of bacterial infections. The nanocomposite exhibits an impressive antimicrobial activity that leads to the complete annihilation of a wide spectrum of Gram‐positive, Gram‐negative, and drug‐resistant bacteria.